Determinants Of the Use of Agency Level Finalcial Application Systems (Sakti): Development of The Umega Model - khabibi, Mohammad wildan; Rosidi (Accounting Department,, 2022)
Purpose — This study examines and analyzes the effect of performance expectancy, effort expectancy, social influence, perceived risk, information quality, system quality, attitude, intention to use, and use of SAKTI. Design/methodology/approach—Data was obtained through online questionnaires filled out by 149 users at the operator level of SAKTI. The analysis method used is Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) test tool. Findings — Empirical evidence shows that performance expectancy, social influence, perceived risk, information quality, system quality, attitude, intention to use, and use of SAKTI affect attitude toward using SAKTI. Intention to use the application affects the use of SAKTI. Practical implications—The SAKTI application will be accepted and used if it increases employee performance, is easy to use, the environment affects usage, is secure, generates information that is simple for users to comprehend and has a good network infrastructure. Application providers can use this research to determine SAKTI usage behaviour. Originality/value—This study develops the UMEGA model to determine the acceptance of the SAKTI application based on attitudes, interests, and usage. Keywords — Accounting; System; SAKTI; UMEGA; and Use of SAKTI Paper type — Case study